2008
DOI: 10.1016/j.metabol.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term exercise and energy surplus on hormones related to regulation of energy balance

Abstract: Energy surplus raises circulating concentrations of leptin and insulin while lowering plasma ghrelin. Exercise has the opposite effects. The purpose of this study was to determine whether exercise counters the hormonal effects of energy surplus independent of changes in energy balance. To do that, we assessed plasma concentrations of leptin, insulin, and ghrelin at baseline, after overfeeding, and after overfeeding plus exercise. Baseline (B) leptin and insulin concentrations and ghrelin area under the curve w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 35 publications
6
34
1
3
Order By: Relevance
“…It is perhaps surprising that acylated ghrelin concentrations were not elevated toward the end of the exercise trials, since energy intake was not increased in these trials to compensate for the energy expended during exercise. These data are consistent with the recent finding that postexercise ghrelin responses may be independent of energy balance (22) and lend support to previous research that indicated acute exercise does not increase energy intake in the short term, i.e., 1 to 2 days after exercise (6,7,24,28,29). It would be of interest to examine acylated ghrelin concentrations the day after exercise to assess whether values are elevated in response to a shortterm negative energy balance.…”
Section: Discussionsupporting
confidence: 92%
“…It is perhaps surprising that acylated ghrelin concentrations were not elevated toward the end of the exercise trials, since energy intake was not increased in these trials to compensate for the energy expended during exercise. These data are consistent with the recent finding that postexercise ghrelin responses may be independent of energy balance (22) and lend support to previous research that indicated acute exercise does not increase energy intake in the short term, i.e., 1 to 2 days after exercise (6,7,24,28,29). It would be of interest to examine acylated ghrelin concentrations the day after exercise to assess whether values are elevated in response to a shortterm negative energy balance.…”
Section: Discussionsupporting
confidence: 92%
“…Although the intensity was similar during the three performance tests in current study, only the second test that was performed after high-volume trainings induced a signiWcant decrease in leptin. This was probably due to the increasing negative energy balance in the organism as discussed before ) and seems to conWrm the previous Wndings that the energy balance is the main factor for changes in leptin during the exercise (Karamouzis et al 2002;Hagobian et al 2008).…”
Section: Discussionsupporting
confidence: 88%
“…The real-world impact of these male-female differences in hormones that regulate energy intake will depend upon if/how these effects manifested over time. The hormones that regulate energy intake respond quickly to alterations in energy status, well prior to measurable changes in body fat (3,18,38). If the hormonal pattern of changes that we observed is maintained over time, body fat loss may be accentuated in men compared with women.…”
Section: Discussionmentioning
confidence: 80%
“…We have previously described a similar protocol to accurately estimate energy intake and expenditure (3,17,18). Prior to the intervention, all subjects completed a diet survey to provide an initial estimate of energy intake.…”
Section: Methodsmentioning
confidence: 99%